Preparation method of graphene-carbon nanotube hybrid oil absorption material
By preparing graphene-carbon nanotube hybrid foam materials and grafting octamine on its surface, the challenges in the molding and oil absorption efficiency of existing graphene foam materials are solved, and efficient oil-fouling adsorption and good recycling performance are achieved. .
Patent Information
- Application Number
- CN202411174268.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-08-26
AI Technical Summary
Existing graphene foam materials have challenges in molding and oil absorption efficiency, and the preparation process is cumbersome and difficult to achieve large-scale application.
By preparing graphene-carbon nanotube hybrid foam materials, graphene oxide foam is used for modification treatment, and carbon nanotubes are grown on the graphene surface by chemical vapor deposition method to increase the specific surface area of the material. Octadecine is then grafted on the surface of the material to improve oil absorption performance.
The oil absorption rate and recycling performance of graphene-carbon nanotube hybrid foam materials were significantly improved, with the oil absorption rate reaching 49.7g/g and the circulation adsorption rate remained above 75%.
Smart Images

Figure CN119425619A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of surface treatment of graphene oxide and chemical vapor deposition, and in particular to a method for preparing a graphene-carbon nanotube hybrid oil-absorbing material. Background Art
[0002] There is a risk of leakage during the extraction, refining, storage, transportation and use of petroleum and its products, and oil pollution can cause great damage to the freshwater ecological environment and the marine ecological environment. Therefore, it is urgent to develop oil-absorbing materials that can quickly, efficiently and simply remove oil pollution and can be recycled after treatment.
[0003] Physical adsorption oil removal has been widely used due to its advantages of low cost, low pollution, recyclability and simple operation. Traditional adsorbent materials are often amphiphilic, with poor selective adsorption and need surface hydrophobic treatment. Graphene has a large specific surface area and oleophilic and hydrophobic properties. At the same time, graphene can generate strong van der Waals forces with organic pollutants such as petroleum, has a strong adsorption capacity for organic pollutants, and is easy to recycle and reuse. Graphene can be used as a modified material for oil-absorbing materials or as a matrix material, showing broad application prospects in the fields of oil absorption and oil-water separation. Due to the inherent rigidity of carbon-based materials, graphene-based foams often introduce organic molecular flexible cross-linking agents to improve their compressibility and oil absorption performance, but due to the cumbersome preparation process, it is difficult to achieve large-scale application. In addition, the introduction of organic molecules will also reduce the content of graphene in the material, which will also affect the final oil absorption effect. In addition, although graphene foam materials have achieved certain results and progress as oil-absorbing materials, graphene foams still face huge challenges in terms of molding and oil absorption efficiency. Summary of the invention
[0004] In order to solve one or more technical problems existing in the prior art, the present invention provides a method for preparing a graphene-carbon nanotube hybrid oil-absorbing material.
[0005] The technical solution of the present invention to solve the above technical problem is as follows: A method for preparing a graphene-carbon nanotube hybrid oil-absorbing material comprises the following steps:
[0006] S1, preparation of graphene oxide foam;
[0007] S2, preparing modified graphene oxide foam by using the graphene oxide foam;
[0008] S3, preparing a graphene-carbon nanotube hybrid foam material: placing the prepared modified graphene oxide foam in a tubular furnace for heating, and introducing argon into the tubular furnace at the same time, when the tubular furnace is heated to a first preset temperature, introducing hydrogen into the tubular furnace, after the tubular furnace is heated to a second preset temperature and stabilized for a first preset time, introducing ferrocene / xylene solution (obtained by mixing ferrocene and xylene) into the tubular furnace through an injection pump as a catalyst, when aerosol appears in the tubular furnace, introducing acetylene into the tubular furnace, after introducing acetylene for a second preset time, closing the acetylene channel and the injection pump, and simultaneously closing the temperature control system of the tubular furnace, closing the hydrogen channel when the tubular furnace is naturally cooled to a third preset temperature, closing the argon channel when the tubular furnace is naturally cooled to a fourth preset temperature, and taking out the sample after the tubular furnace is naturally cooled to room temperature, thereby obtaining a graphene-carbon nanotube hybrid foam material;
[0009] S4, grafting octadecylamine: preparing an octadecylamine grafting preparatory solution, immersing the prepared graphene-carbon nanotube hybrid foam material in the octadecylamine grafting preparatory solution, heating for a third preset time, and freeze-drying to obtain the graphene-carbon nanotube hybrid oil-absorbing material grafted with octadecylamine.
[0010] The beneficial effects of the present invention are as follows: the preparation method of the present invention is to centrifuge and wash a commercially available graphene oxide solution, and prepare it into graphene oxide foam, dissolve the washed graphene oxide foam in water and ethanol, and drop ethyl orthosilicate under alkaline conditions to deposit a layer of silicon dioxide on the surface of the graphene oxide. The presence of silicon dioxide can make carbon nanotubes grow uniformly on the surface of the graphene oxide. Subsequently, a chemical vapor deposition method is adopted to grow carbon nanotubes on the surface of the graphene oxide using acetylene as a carbon source to increase the specific surface area of the graphene foam, and then the graphene oxide is subjected to high-temperature reduction to prepare a graphene / carbon nanotube hybrid material. Subsequently, long-chain alkane octadecylamine is grafted on the surface of the graphene / carbon nanotube hybrid material using polydopamine as a medium, thereby obtaining a carbon-based material with high oil absorption and good circulation performance.
[0011] Based on the above technical solution, the present invention can also be improved as follows.
[0012] Furthermore, in S3, the introduction rate of the argon gas is 200-600 ml / min, the introduction rate of the hydrogen gas is 80-120 ml / min, the introduction rate of the acetylene is 5-20 ml / min, the propulsion rate of the injection pump is 0.1-0.5 ml / min, and the concentration of the catalyst is 0.01-0.1 g / mL.
[0013] Furthermore, the introduction rate of the argon gas is 400 ml / min, the introduction rate of the hydrogen gas is 90 ml / min, the introduction rate of the acetylene is 10 ml / min, the propulsion rate of the injection pump is 0.2 ml / min, and the concentration of the catalyst is 0.05 g / mL.
[0014] Further, in S3, the heating rate of the temperature control system of the tubular furnace is 10-25°C / min; the first preset temperature is 200°C, the second preset temperature is 750°C, the first preset time is 5min, the second preset time is 5-20min, the third preset temperature is 500°C, and the fourth preset temperature is 100°C.
[0015] Furthermore, the heating rate of the temperature control system of the tubular furnace is 20°C / min, and the second preset time is 15 minutes.
[0016] The beneficial effect of adopting the above further scheme is that when acetylene is introduced for 15 minutes, almost all of the graphene oxide sheets are covered by carbon nanotubes, and the carbon nanotubes grow more densely and have a longer length, about 40 μm. Graphene oxide grows vertically on the surface of graphene oxide, and due to the coverage of carbon nanotubes, it is difficult to observe the edge of graphene oxide.
[0017] Furthermore, in S4, the preparation method of the octadecylamine grafting preparatory solution is: dissolving octadecylamine in anhydrous ethanol to prepare an octadecylamine solution of 1 to 5 mg / ml, adding Tris solution, stirring and then adding dopamine hydrochloride, stirring to obtain an octadecylamine grafting preparatory solution with a dopamine hydrochloride concentration of 1 to 5 mg / ml.
[0018] Furthermore, the configuration ratio of the octadecylamine solution to the Tris solution is 1:4, which is the mass ratio of octadecylamine to Tris.
[0019] Further, in S4, the prepared graphene-carbon nanotube hybrid foam material is immersed in the octadecylamine grafting preparatory solution and then heated in a 50° C. water bath for 4 to 12 hours.
[0020] Further, in S3, the prepared modified graphene oxide foam is spread on the quartz glass. The laying is done naturally, and there is no requirement for the laying thickness, for example, about 1 cm is sufficient. The quartz glass is placed in the middle position of the tubular furnace for heating.
[0021] Further, in S2, the preparation process of modified graphene oxide foam prepared by using the graphene oxide foam is as follows: ultrasonically disperse the graphene oxide foam in a mixture of anhydrous ethanol and deionized water (the volume ratio of anhydrous ethanol to deionized water is 8:1), and after it is completely dispersed, adjust the pH value to 9-10, then add tetraethyl orthosilicate, seal the cup mouth with a plastic film, and react at room temperature for 12-24 hours; after the reaction is completed, add anhydrous ethanol to wash and centrifuge for 2-3 times, mix the obtained precipitate with deionized water, and ultrasonically disperse it at room temperature for 30 minutes, then ultrasonically crush it for 20 minutes, and freeze-dry to obtain modified graphene oxide foam.
[0022] The present invention directly tests the oil absorption rate of graphene oxide and graphene-carbon nanotube hybrid oil-absorbing material. The oil absorption rate of graphene-carbon nanotube hybrid foam material for hydroxyl silicone oil is about 12 g / g, the adsorption rate of graphene oxide foam for hydroxyl silicone oil is about 7 g / g, and the oil absorption rate of graphene / carbon nanotube hybrid oil-absorbing material grafted with ODA is 49.7 g / g. It can be seen that the adsorption rate of graphene-carbon nanotube hybrid foam material for hydroxyl silicone oil is higher than that of graphene oxide, almost twice of the latter, and the introduction of ODA significantly improves the oil absorption rate of the foam material. This is mainly because the growth of carbon nanotubes CNT constructs a hydrophobic nano multi-level structure, and the introduction of ODA increases the hydrophobic surface. The two synergistically give the foam material significantly improved oil absorption performance. The test results of the cyclic adsorption rate of the graphene-carbon nanotube hybrid oil-absorbing material show that even after three cycles of use, the cyclic adsorption rate of the graphene-carbon nanotube hybrid oil-absorbing material remains above 75%, so it has good recycling performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the SEM image of graphene oxide foam in Example 1;
[0024] Figure 2 is the XRD pattern of graphene oxide foam of Example 1;
[0025] Figure 3 This is a SEM image of the modified graphene oxide foam with silicon dioxide deposited on the surface of Example 2;
[0026] Figure 4 is a SEM image of the graphene-carbon nanotube hybrid foam material in Example 3;
[0027] Figure 5 is the XRD pattern of the graphene-carbon nanotube hybrid foam material in Example 4;
[0028] Figure 6 This is the SEM image of the graphene-carbon nanotube hybrid foam material in Example 4. DETAILED DESCRIPTION
[0029] The principles and features of the present invention are described below in conjunction with the accompanying drawings. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0030] Example 1
[0031] Commercially available graphene oxide was used to prepare graphene oxide foam by freeze drying as a control material. Specifically, the graphene oxide solution (which can be prepared by conventional methods) was poured into a centrifuge tube, shaken evenly and placed in a centrifuge, and the centrifuge conditions were set to 8000 rpm for 30 minutes. Then the upper clear liquid was sucked out with a rubber-tipped dropper, centrifuged with deionized water until the pH was between 5 and 6, and the centrifuge tube was placed in a -85°C refrigerator for 24 hours, and then placed in a freeze dryer for 48 hours to obtain graphene oxide foam.
[0032] The obtained graphene oxide foam material was ultrasonically dispersed in anhydrous ethanol and then dropped onto a silicon wafer. After evaporating the ethanol, a SEM picture of the graphene oxide foam material was taken by scanning electron microscopy (scanning electron microscope observation (TESCANMIRALMS, Czech Republic, TESCAN Ltd.)). The XRD spectrum of the graphene oxide foam material was directly obtained by an X-ray diffractometer (X'Pert PRO MPD, PANalytical, the Netherlands) with a scanning range of 5-90° and a scanning speed of 5° / min.
[0033] Figure 1 This is a SEM image of graphene oxide foam, which shows that graphene oxide is an irregular flake structure with a size of less than 100 μm. The flake structure is translucent, indicating that it is thin. The surface of graphene oxide is relatively clean and has no other impurities. Figure 2 This is the XRD diagram of graphene oxide foam. From the figure, we can see that the characteristic diffraction peak of graphene oxide appears at 2θ=11.56°, and the peak is sharp.
[0034] Example 2
[0035] Pour the graphene oxide solution into a centrifuge tube, shake it evenly and put it into a centrifuge, set the centrifuge conditions to 8000 rpm for 30 minutes. Then use a rubber-tipped dropper to suck out the supernatant, centrifuge it with deionized water until the pH is between 5 and 6, put the centrifuge tube into a -85°C refrigerator and freeze it for 24 hours, then put it into a freeze dryer and dry it for 48 hours to obtain graphene oxide foam.
[0036] Ultrasonic dispersion of graphene oxide foam in anhydrous ethanol and deionized water mixture (0.5 mg / mL), after complete dispersion, magnetic stirring at room temperature, while adding ammonia water with a rubber dropper to adjust the pH value to 9-10, then adding 2 mL of ethyl orthosilicate, sealing the cup mouth with plastic film, and reacting at room temperature for 16 hours. After the reaction is completed, the liquid is transferred to a centrifuge tube, and after adding an appropriate amount of ethanol, it is shaken evenly, centrifuged at 8000 rpm for 10 minutes. The upper clear liquid is sucked out with a rubber dropper, and then washed with anhydrous ethanol and centrifuged 2-3 times. The obtained precipitate is mixed with a certain amount of deionized water and ultrasonically dispersed at room temperature for 30 minutes, then ultrasonically crushed for 20 minutes and placed in a refrigerator for 24 hours, and freeze-dried for 48 hours to obtain modified graphene oxide foam.
[0037] Figure 3 This is a SEM image of graphene oxide with silicon dioxide deposited on the surface. Figure 3 As shown, after a layer of silicon dioxide is deposited, the shape of the graphene oxide sheet is almost unchanged and it is also in a translucent state, indicating that the deposited silicon dioxide layer is very thin. The method and instrument for obtaining the SEM image and XRD spectrum in this example are the same as those in Example 1.
[0038] Example 3
[0039] Pour the graphene oxide solution into a centrifuge tube, shake it evenly and put it into a centrifuge, set the centrifuge conditions to 8000 rpm for 30 minutes. Then use a rubber-tipped dropper to suck out the supernatant, centrifuge it with deionized water until the pH is between 5 and 6, put the centrifuge tube into a -85°C refrigerator and freeze it for 24 hours, then put it into a freeze dryer and dry it for 48 hours to obtain graphene oxide foam.
[0040] Ultrasonic dispersion of graphene oxide foam in anhydrous ethanol and deionized water mixture (0.5 mg / mL), after complete uniform dispersion, magnetic stirring was performed at room temperature, and ammonia water was added with a rubber-tipped dropper to adjust the pH value to 9-10, followed by addition of 2 mL of ethyl orthosilicate, and the cup mouth was sealed with a plastic film, and the reaction was carried out at room temperature for 16 hours. After the reaction, the liquid was transferred to a centrifuge tube, and after adding an appropriate amount of ethanol, it was shaken evenly, centrifuged at 8000 rpm for 10 minutes. The upper clear liquid was sucked out with a rubber-tipped dropper, and then washed with anhydrous ethanol and centrifuged 2-3 times. The obtained precipitate was mixed with a certain amount of deionized water and ultrasonically dispersed at room temperature for 30 minutes, then ultrasonically crushed for 20 minutes and placed in a refrigerator for 24 hours, and freeze-dried for 48 hours to obtain modified graphene oxide foam.
[0041] The prepared modified graphene oxide foam was spread on the quartz glass, and the introduction rates of argon (400 ml / min), hydrogen (90 ml / min), and acetylene (10 ml / min) were set at the same time. The pre-prepared ferrocene-xylene mixed solution (reaction catalyst, 0.05 g / mL) was installed on the syringe pump, and the advancement rate was set to 0.2 ml / min. The quartz glass with the modified graphene oxide foam was placed in the middle position of the tube furnace, and the temperature control program of the tube furnace was set and heating was started. The heating rate was 20 ° C / min, and argon was introduced at the set rate at the same time. When the temperature was raised to 2 At 100°C, hydrogen is introduced at a set rate. When the temperature reaches 750°C, after the temperature stabilizes for 5 minutes, ferrocene / xylene solution is introduced as a catalyst (200 μL) at a set rate. When the amount of catalyst introduced reaches a certain amount and aerosol appears in the tube, acetylene is introduced at a set rate for reaction and timing is started. After 5 minutes of acetylene introduction, the acetylene channel is closed, the injection pump is turned off, the temperature control program of the tubular furnace is turned off, and the hydrogen is turned off when it is naturally cooled to 500°C. The argon channel is closed when it is naturally cooled to 100°C. After cooling to room temperature, the sample can be taken out to obtain the graphene / carbon nanotube hybrid material.
[0042] Figure 4 The SEM image of the graphene / carbon nanotube hybrid material shows that only a small portion of the graphene oxide surface is attached with carbon nanotubes, and the surface of the other portion of the graphene oxide is still smooth without carbon nanotubes. The length of the carbon nanotubes attached to the graphene oxide surface is also less than 10um. This is because the acetylene is introduced for a short time, and the number and length of the carbon nanotubes grown on the graphene oxide surface are limited. Not only is the length small, but it is also unable to completely cover the graphene oxide surface. The method and instrument for obtaining the SEM image and XRD spectrum of this embodiment are the same as those of Example 1.
[0043] Example 4
[0044] Pour the graphene oxide solution into a centrifuge tube, shake it evenly and put it into a centrifuge, set the centrifuge conditions to 8000 rpm for 30 minutes. Then use a rubber-tipped dropper to suck out the supernatant, centrifuge it with deionized water until the pH is between 5 and 6, put the centrifuge tube into a -85°C refrigerator and freeze it for 24 hours, then put it into a freeze dryer and dry it for 48 hours to obtain graphene oxide foam.
[0045] Ultrasonic dispersion of graphene oxide foam in anhydrous ethanol and deionized water mixture (0.5 mg / mL), after complete dispersion, magnetic stirring at room temperature, while adding ammonia water with a rubber dropper to adjust the pH value to 9-10, then adding 2 mL of ethyl orthosilicate, sealing the cup mouth with plastic film, and reacting at room temperature for 16 hours. After the reaction is completed, the liquid is transferred to a centrifuge tube, and after adding an appropriate amount of ethanol, it is shaken evenly, centrifuged at 8000 rpm for 10 minutes. The upper clear liquid is sucked out with a rubber dropper, and then washed with anhydrous ethanol and centrifuged 2-3 times. The obtained precipitate is mixed with a certain amount of deionized water and ultrasonically dispersed at room temperature for 30 minutes, then ultrasonically crushed for 20 minutes and placed in a refrigerator for 24 hours, and freeze-dried for 48 hours to obtain modified graphene oxide foam.
[0046] The prepared modified graphene oxide foam was spread on the quartz glass, and the introduction rates of argon (400 ml / min), hydrogen (90 ml / min), and acetylene (10 ml / min) were set at the same time. The pre-prepared ferrocene-xylene mixed solution (reaction catalyst, 0.05 g / mL) was installed on the syringe pump, and the advancement rate was set to 0.2 ml / min. The quartz glass with the modified graphene oxide foam was placed in the middle position of the tube furnace, and the temperature control program of the tube furnace was set and heating was started. The heating rate was 20 ° C / min, and argon was introduced at the set rate at the same time. When the temperature was raised to 20 At 0°C, hydrogen is introduced at a set rate. When the temperature is raised to 750°C, after the temperature is stabilized for 5 minutes, ferrocene / xylene solution is introduced as a catalyst (200 μL) at a set rate. When the amount of the catalyst introduced reaches a certain amount and aerosol appears in the tube, acetylene is introduced at a set rate for reaction and timing is started. After 15 minutes of acetylene introduction, the acetylene channel is closed, the injection pump is turned off, the temperature control program of the tubular furnace is turned off, and the hydrogen is turned off when it is naturally cooled to 500°C. The argon channel is closed when it is naturally cooled to 100°C. After cooling to room temperature, the sample can be taken out to obtain a graphene-carbon nanotube hybrid foam material.
[0047] Figure 5 This is the XRD diagram of the graphene / carbon nanotube hybrid material. In addition to the characteristic diffraction peak of graphene oxide at 2θ=11.56°, the graphene / carbon nanotube hybrid material also has a sharp characteristic diffraction peak at 2θ=25.94°. Carbon nanotubes were successfully grown on the GO@SiO2 surface using the CVD process (under alkaline conditions, ethyl orthosilicate is hydrolyzed in a graphene oxide dispersion, and then the silicon-oxygen bonds in the hydrolysis product react with the oxygen-containing functional groups on the graphene oxide surface to deposit a layer of silicon dioxide on the graphene oxide surface. GO@SiO2 represents a layer of silicon dioxide deposited on the graphene oxide surface.), and the graphene / carbon nanotube hybrid material was successfully prepared. Figure 6This is a SEM image of graphene / carbon nanotube hybrid material. The results show that after 15 minutes of acetylene injection, almost all graphene oxide sheets are covered by carbon nanotubes, and the carbon nanotubes grow denser and longer, about 40μm. Graphene oxide grows vertically on the surface of graphene oxide, and it is difficult to observe the edge of graphene oxide due to the coverage of carbon nanotubes.
[0048] The method and instrument for obtaining the SEM images and XRD patterns in this example are the same as those in Example 1.
[0049] Example 5
[0050] Pour the graphene oxide solution into a centrifuge tube, shake it evenly and put it into a centrifuge, set the centrifuge conditions to 8000 rpm for 30 minutes. Then use a rubber-tipped dropper to suck out the supernatant, centrifuge it with deionized water until the pH is between 5 and 6, put the centrifuge tube into a -85°C refrigerator and freeze it for 24 hours, then put it into a freeze dryer and dry it for 48 hours to obtain graphene oxide foam.
[0051] Ultrasonic dispersion of graphene oxide foam in anhydrous ethanol and deionized water mixture (0.5 mg / mL), after complete dispersion, magnetic stirring at room temperature, while adding ammonia water with a rubber dropper to adjust the pH value to 9-10, then adding 2 mL of ethyl orthosilicate, sealing the cup mouth with plastic film, and reacting at room temperature for 16 hours. After the reaction is completed, the liquid is transferred to a centrifuge tube, and after adding an appropriate amount of ethanol, it is shaken evenly, centrifuged at 8000 rpm for 10 minutes. The upper clear liquid is sucked out with a rubber dropper, and then washed with anhydrous ethanol and centrifuged 2-3 times. The obtained precipitate is mixed with a certain amount of deionized water and ultrasonically dispersed at room temperature for 30 minutes, then ultrasonically crushed for 20 minutes and placed in a refrigerator for 24 hours, and freeze-dried for 48 hours to obtain modified graphene oxide foam.
[0052] The prepared modified graphene oxide foam was spread on the quartz glass, and the introduction rates of argon (400 ml / min), hydrogen (90 ml / min), and acetylene (10 ml / min) were set at the same time. The pre-prepared ferrocene-xylene mixed solution (reaction catalyst, 0.05 g / mL) was installed on the syringe pump, and the advancement rate was set to 0.2 ml / min. The quartz glass with the modified graphene oxide foam was placed in the middle position of the tube furnace, and the temperature control program of the tube furnace was set and heating was started. The heating rate was 20 ° C / min, and argon was introduced at the set rate at the same time. When the temperature was raised to 2 At 100°C, hydrogen is introduced at a set rate. When the temperature reaches 750°C, after the temperature stabilizes for 5 minutes, ferrocene / xylene solution is introduced as a catalyst (200 μL) at a set rate. When the amount of catalyst introduced reaches a certain amount and aerosol appears in the tube, acetylene is introduced at a set rate for reaction and timing is started. After 15 minutes of acetylene introduction, the acetylene channel is closed, the injection pump is turned off, the temperature control program of the tubular furnace is turned off, and the hydrogen is turned off when it is naturally cooled to 500°C. The argon channel is closed when it is naturally cooled to 100°C. After cooling to room temperature, the sample can be taken out to obtain the graphene-carbon nanotube hybrid material.
[0053] Dissolve octadecylamine (ODA) in anhydrous ethanol (stir for 30 minutes) to prepare a 2.5 mg / ml ODA solution, add Tris solution at a ratio of 1:4, stir, then add dopamine hydrochloride (DA) to make its concentration 2 mg / ml, stir for 30 minutes. Immerse the prepared graphene / carbon nanotube hybrid material in the solution, heat it in a 50°C water bath for 6 hours, and freeze-dry it for 48 hours to obtain the graphene-carbon nanotube hybrid oil-absorbing material grafted with octadecylamine.
[0054] The oil absorption rates of the graphene oxide foam obtained in Example 1, the graphene-carbon nanotube hybrid foam material obtained in Example 4, and the graphene-carbon nanotube hybrid oil-absorbing material grafted with octadecylamine obtained in Example 5 were tested as shown in Table 1.
[0055] The specific test method is to spread a certain mass m0 of graphene-carbon nanotube hybrid foam material with a CVD time of 15min (Example 4) and freeze-dried graphene oxide foam (Example 1) on laboratory gauze and fold it into a shape similar to a tea bag. At the same time, a clean laboratory gauze is also folded into a shape similar to a tea bag as a blank control. Weigh the three "tea bags" with an electronic balance and record the data m1, m2, and m3. Take three clean beakers, put the three "tea bags" in respectively, and number the three beakers. Only the gauze is marked as ①, the beaker with graphene oxide foam is marked as ②, and the beaker with graphene-carbon nanotube hybrid foam material is marked as ③. Pour an appropriate amount of hydroxy silicone oil into the three beakers until the hydroxy silicone oil can immerse the "tea bag", then put the three beakers on an electronic balance for weighing, and record the data m 11 、m 22 、m 33 After soaking for a certain period of time, use tweezers to pick up the three "tea bags" and separate them from the hydroxy silicone oil, then drain them above the beaker for the same period of time, then remove the three "tea bags", place ①, ②, ③, and the beaker on an electronic balance for weighing, and record the data. 111 、m 222 、m 333 The saturated oil absorption rate of laboratory gauze can be calculated using formula (1).
[0056]
[0057] Q1 is the saturated oil absorption rate of the laboratory gauze (since the tea bag is folded from gauze, the saturated oil absorption rate of the gauze can be calculated to deduct the blank absorption as a carrier of the graphene-carbon nanotube hybrid foam material, and the influence of irrelevant variables on the test results), and then the weight of the other two "tea bag" gauzes can be calculated by calculation, and their oil absorption can be calculated, and then the oil absorption of the "tea bag" minus the oil absorption of the gauze can be obtained to obtain the sample oil absorption, and finally the oil absorption rate of the sample is calculated. Example 5 The oil absorption rate calculation method is the same as above.
[0058] Graphene-carbon nanotube hybrid foam material cyclic oil absorption test: squeeze the "tea bag" in beaker No. ③, repeat the above test method to test, and determine the recycling performance of the graphene-carbon nanotube hybrid material, as shown in Table 3.
[0059] Table 1
[0060] sample Oil absorption rate (g / g) Example 1 6.691 Example 4 11.849 Example 5 49.700
[0061] Table 2
[0062] sample Water contact Example 1 100° Example 4 112° Example 5 122°
[0063] Table 3
[0064] Cycle times Cycle oil absorption rate (%) 1 95 2 85 3 77
[0065] Table 1 is the oil absorption rate data of Example 1, Example 4 and Example 5. The results show that after chemical vapor deposition of carbon nanotubes and reduction, the oil absorption of graphene foam has been significantly improved compared with graphene oxide. Table 2 is the contact angle of the materials of Example 1, Example 4 and Example 5. The results show that the introduction of carbon nanotubes CNT improves the hydrophobicity of graphene foam materials. Because the presence of the silicon dioxide deposition layer helps the uniform deposition of CNT on the surface of graphene oxide, and the hydrophobic nano multi-level structure constructed by graphene oxide and CNT is conducive to the improvement of the oil absorption performance of the material. Table 3 is the cyclic oil absorption efficiency of Example 4. The results show that even after three cycles, the cyclic adsorption rate of the graphene / carbon nanotube hybrid material remains above 75%, so it has good recycling performance.
[0066] As shown in Table 1, the oil absorption of the composite foam material of Example 5 is much higher than that of Example 4 and Example 1. Table 2 shows the contact angles of the materials of Example 1, Example 4 and Example 5. The data show that the introduction of ODA will further increase the hydrophobicity of the material. The introduction of ODA will increase the hydrophobicity of the material surface on the basis of Example 4, thereby improving the adsorption capacity of oil, which also indirectly illustrates the successful grafting of ODA.
[0067] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0068] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a graphene-carbon nanotube hybrid oil-absorbing material, characterized in that: The following steps are involved: S1, preparation of graphene oxide foam; S2, preparing modified graphene oxide foam by using the graphene oxide foam; S3, preparing a graphene-carbon nanotube hybrid foam material: placing the prepared modified graphene oxide foam in a tubular furnace for heating, and introducing argon into the tubular furnace at the same time, when the tubular furnace is heated to a first preset temperature, introducing hydrogen into the tubular furnace, and after the tubular furnace is heated to a second preset temperature and stabilized for a first preset time, introducing a ferrocene / xylene solution as a catalyst into the tubular furnace through an injection pump, and when aerosol appears in the tubular furnace, introducing acetylene into the tubular furnace, and after introducing acetylene for a second preset time, closing the acetylene channel and the injection pump, and simultaneously closing the temperature control system of the tubular furnace, and when the tubular furnace is naturally cooled to a third preset temperature, closing the hydrogen channel, and when the tubular furnace is naturally cooled to a fourth preset temperature, closing the argon channel, and taking out the sample after the tubular furnace is naturally cooled to room temperature, thereby obtaining a graphene-carbon nanotube hybrid foam material; S4, grafting octadecylamine: preparing an octadecylamine grafting preparatory solution, immersing the prepared graphene-carbon nanotube hybrid foam material in the octadecylamine grafting preparatory solution, heating for a third preset time, and freeze-drying to obtain the graphene-carbon nanotube hybrid oil-absorbing material grafted with octadecylamine.
2. The method for preparing a graphene-carbon nanotube hybrid oil-absorbing material according to claim 1, characterized in that: In S3, the introduction rate of the argon gas is 200-600 ml / min, the introduction rate of the hydrogen gas is 80-120 ml / min, the introduction rate of the acetylene is 5-20 ml / min, the propulsion rate of the injection pump is 0.1-0.5 ml / min, and the concentration of the catalyst is 0.01-0.1 g / mL.
3. The method for preparing a graphene-carbon nanotube hybrid oil-absorbing material according to claim 2, characterized in that: The introduction rate of the argon gas was 400 ml / min, the introduction rate of the hydrogen gas was 90 ml / min, the introduction rate of the acetylene was 10 ml / min, the propulsion rate of the injection pump was 0.2 ml / min, and the concentration of the catalyst was 0.05 g / mL.
4. The method for preparing a graphene-carbon nanotube hybrid oil-absorbing material according to claim 1, characterized in that: In S3, the heating rate of the temperature control system of the tubular furnace is 10-25°C / min; the first preset temperature is 200°C, the second preset temperature is 750°C, the first preset time is 5min, the second preset time is 5-20min, the third preset temperature is 500°C, and the fourth preset temperature is 100°C.
5. The method for preparing a graphene-carbon nanotube hybrid oil-absorbing material according to claim 4, characterized in that: The heating rate of the temperature control system of the tube furnace is 20° C. / min, and the second preset time is 15 min.
6. The method for preparing a graphene-carbon nanotube hybrid oil-absorbing material according to claim 1, characterized in that: In S4, the preparation method of the octadecylamine grafting preparatory solution is: dissolving octadecylamine in anhydrous ethanol to prepare a 1-5 mg / ml octadecylamine solution, adding Tris solution, stirring, and then adding dopamine hydrochloride to obtain an octadecylamine grafting preparatory solution with a concentration of 1-5 mg / ml after stirring.
7. The method for preparing a graphene-carbon nanotube hybrid oil-absorbing material according to claim 6, characterized in that: The configuration ratio of the octadecylamine solution to the Tris solution is 1:
4.
8. The method for preparing a graphene-carbon nanotube hybrid oil-absorbing material according to claim 1, characterized in that: In S4, the prepared graphene-carbon nanotube hybrid foam material is immersed in the octadecylamine grafting preparatory solution and then heated in a 50° C. water bath for 4 to 12 hours.
9. The method for preparing a graphene-carbon nanotube hybrid oil-absorbing material according to claim 1, characterized in that: In S3, the prepared modified graphene oxide foam is spread on the quartz glass, and the quartz glass is placed in the middle position of the tube furnace for heating.
10. The method for preparing a graphene-carbon nanotube hybrid oil-absorbing material according to claim 1, characterized in that: In S2, the preparation process of modified graphene oxide foam prepared by using the graphene oxide foam is as follows: ultrasonically disperse the graphene oxide foam in a mixture of anhydrous ethanol and deionized water, and after it is completely dispersed, adjust the pH value to 9-10, then add tetraethyl orthosilicate, seal the cup mouth with a plastic film, and react at room temperature for 12-24 hours; after the reaction is completed, add anhydrous ethanol to wash and centrifuge for 2-3 times, mix the obtained precipitate with deionized water, and ultrasonically disperse it at room temperature for 30 minutes, then ultrasonically crush it for 20 minutes, and freeze-dry to obtain modified graphene oxide foam.
Citation Information
Patent Citations
Preparation method for copolymerization living polymer modified graphene oxide
CN105199436A
Method for direct growth of porous carbon nanotube graphene hybrid on nano-porous copper
CN105645376A
Three dimensional graphene oxide foamed material preparation method through natural drying of solution
CN109205609A
Graphene foam-protected metal fluoride and metal chloride cathode active materials for lithium batteries
CN110366792A
Preparation method of super-hydrophobic oleophylic material
CN110755888A